Bimetallic Ni-M (M = Co, Cu and Zn) supported on attapulgite as catalysts for hydrogen production from glycerol steam reforming - Wang, Y.; Chen, M.; Yang, Z.; Liang, T.; Liu, Shaomin; Zhou, Z.; Li, X. (2018)
Monometallic Ni and bimetallic Ni-Co, Ni-Cu, and Ni-Zn catalysts supported on attapulgite (ATP) were prepared by chemical precipitation method and evaluated in the glycerol steam reforming (GSR) reaction under the following conditions W/G = 9, N 2 flow ratio = 0.16 L/min and GHSV = 9619 h -1 . The prepared calcined and/or reduced samples were characterized by ICP-OES, N 2 adsorption-desorption, XRD, TEM, FT-IR, XPS and H 2 -TPR. The analysis results showed the addition of second metals obviously decreased the crystal size and suppressed the reducibility of active metal, by improving the metal-support interaction. These were optimized characters could promote the steam reforming reaction and water-gas shift reaction (WGSR) to improve the catalytic performance. The experimental results of catalytic activity revealed the glycerol conversions and H 2 yields over bimetallic catalysts were significantly higher than those over Ni/ATP catalyst. Among them, the Ni-Cu/ATP exhibited the highest the highest glycerol conversions and H 2 yield in GSR reaction, while it had larger particle size (12.2 nm) than Ni-Co/ATP (8.6 nm) and Ni-Zn/ATP (10.3 nm), and the higher reducibility than other two bimetallic catalysts. It may be deduced that the crystal size and reducibility of catalyst all showed pivotal to impart suitable catalytic activity, while these characteristics should have an optimal proportion for obtaining the outstanding catalytic performance. The effect of temperature on catalytic performance over all catalysts was also investigated. It was found that increasing temperature was favorable for glycerol conversions and H 2 yield, while the increase rate of H 2 /CO ratio was suppressed and CO/CO 2 ratio were increased for all catalysts at high temperature range of 600–700 °C. It was attributed to that increasing temperature although improved the breakage of C[sbnd]C, C[sbnd] H, and C[sbnd]O bonds in glycerol, the WGSR mainly side-reaction for producing H 2 was suppressed. The long-term experiments (30 h) were also conducted over all catalysts at W/G = 9, T = 600 °C, N 2 flow ratio = 0.16 L/min and GHSV = 9619 h -1 . The results demonstrated the outstanding stability was obtained over Ni-Zn/ATP catalyst. In order to account for the causes resulted in catalyst deactivation, all spent catalysts were characterized by XRD, TEM, TPO and TG-DTG. The results shown catalyst deactivation was mainly affected by the sintering of active species and coke formation on catalyst surface. The Ni-Zn/ATP bimetallic catalyst showed the outstanding stability attributed to the excellent anti- sintering and carbon deposition, which resulted from the formation of unique metal-support interaction.